2012
DOI: 10.1080/17470218.2012.685079
|View full text |Cite
|
Sign up to set email alerts
|

Orienting Numbers in Mental Space: Horizontal Organization Trumps Vertical

Abstract: While research on the spatial representation of number has provided substantial evidence for a horizontally oriented mental number line, recent studies suggest vertical organization as well. Directly comparing the relative strength of horizontal and vertical organization, however, we found no evidence of spontaneous vertical orientation (upward or downward), and horizontal trumped vertical when pitted against each other (Experiment 1). Only when numbers were conceptualized as magnitudes (as opposed to nonmagni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 20 publications
9
84
3
Order By: Relevance
“…The latter effect contrasts with those observed in previous studies, in which values were generally found to increase from bottom to top rather than the reverse (e.g., Holmes & Lourenco, 2012;Loetscher et al, 2010; but see Hung et al, Together with the lack of overt spatial cues, this suggests the activation of an MNL stored in long-term memory, as opposed to an ad-hoc spatial representation driven by task demands (cf. Fias, 2015). 2008).…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…The latter effect contrasts with those observed in previous studies, in which values were generally found to increase from bottom to top rather than the reverse (e.g., Holmes & Lourenco, 2012;Loetscher et al, 2010; but see Hung et al, Together with the lack of overt spatial cues, this suggests the activation of an MNL stored in long-term memory, as opposed to an ad-hoc spatial representation driven by task demands (cf. Fias, 2015). 2008).…”
Section: Resultscontrasting
confidence: 56%
“…Thus, after eliminating procedural confounds that may have primed vertical eye movements, horizontal gaze patterns continued to reflect the total hand value and were not driven merely by the last card's value, whereas vertical gaze patterns were weaker and driven solely by the last card's value. Moreover, the observed top-to-bottom orientation is surprising, given the opposite orientation (bottom-to-top) found in previous studies (e.g., Holmes & Lourenco, 2012;Loetscher et al, 2010). Hung et al (2008) found top-to-bottom orientation in Chinese speakers when processing Chinese number words, but our English-speaking participants had no particular experience, linguistic or otherwise, that might be expected to yield such an orientation.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…Many researchers have studied the vertically oriented mental number line in which smaller quantities are on the bottom and larger quantities are on the top (e.g., Holmes & Lourenco, 2012;Ito & Hatta, 2004;Shaki & Fischer, 2012;Wiemers, Bekkering, & Lindemann, 2014). Many claims regarding a horizontal mental number line are applicable to a vertical mental number line if "bottom" is substituted for "left" and "top" is substituted for "right".…”
Section: Notesmentioning
confidence: 99%